Global energy innovation [ why America must lead - Clark, Woodrow W.; Cooke, Grant , 1947- (Praeger, 2012)
The world is entering the Third Industrial Revolution, an era of remarkable progress in science and technology that will require a global shift away from reliance on fossil-fuel and carbon-based energy. This book explains how America can lead the effort to reverse global warming and become the world leader in global energy innovation.